General Review of The Appointment of Active Polri Members to Answer as Regional Head (Case Study: Appointment of Pol Commissioner General Mochamad Iriawan As Acting Governor of West Java.) (International Journal of Psychosocial Rehabilitation, 2020)
This research analyzes the appointment of Pol Commissioner General (Komjen) Pol Mochamad Iriawan as Acting Governor of Answers. Because according to Law No. 2 of 2002 concerning National Police of the Republic of Indonesia, it is stated in Article 28 that members of the police must not involve themselves in practical political activities and if they are going to occupy positions outside the National Police, they must resign. Pol Commissioner General (Komjen) Mochamad Iriawan is still a unit within the Indonesian National Police and where his appointment as Acting Governor of West Java is a proposal of the Ministry of Internal Affairs (Mendagri) which then Commissioner General (Komjen) Pol M Iriawan is appointed as the Acting Governor of West Java in dated 18-06-2018 which was then handled by the president according to the Presidential DecreeNumber 106 / P of 2018 concerning the Inauguration of the Dismissal of the Governor / Deputy Governor of West Java for the 2013-2018 Term and the Appointment of the Acting Governor of West Java. This study uses normative, the author will analyze in the appointment of an active police officer who became Acting Governor of West Java. The results of this study concluded that the appointment of the Minister of Home Affairs made Komjen M Iriawan as Acting Governor of West Java in violation of Law No. 2 of 2002 concerning the Indonesian National Police and Law No. 5 of 2014 concerning State Civil Apparatus. In this Law, all procedures are regulated if a police officer wants to occupy a position within the State Civil Apparatus.